Household welfare and poverty dynamics in Burkina Faso : empirical evidence from household surveys - Fofack, Hippolyte (Policy research working paper, 2001)
The benefits from growth following devaluation of the CFA franc in Burkina Faso in 1994 were undermined by increasing income inequality. Factors that fed that growth in income inequality: disparities in wages and in educational attainment and unequal access to productive assets